The administrative broker: Bureaucratic politics in the era of prevalent information - Lee, JongKon (2013)
Although traditional models of bureaucratic politics have relied on the old assumption that information is expensive, information is prevalent nowadays; the monopoly of bureaucratic expertise has been undermined as interest groups have significantly developed and are professionalized. As a result, what is really important in current bureaucratic politics is not just neutral expertise, but the political capacity to affect the behaviors of information sources. Through mediating conflicts of interest and minimizing unnecessary contingencies, agencies can persuade their stakeholders not to provide information to legislators and, therefore, indirectly affect legislators' decisions on delegation and oversight. Different from traditional principal-agent theories, this article suggests the "administrative broker" model in which politically influential agencies can block information leakage to legislators and enhance their own discretion. Moreover, the administrative brokers occasionally transform traditionally hostile principal-agent relations into more favorable ones. - Reproduced.
Keywords: Bureaucracy